Knowledge, attitude and practice of medical students in Khartoum State, Sudan towards neglected tropical diseases 2023–2024 - a cross-sectional study - Fatima Elbasri Abuelgasim Mohammed; Umniha Siddig Ahmed Elgailani; Ammar Elgadi; Mohamed Elmujtaba Suliman; Eisar Babiker Bakheit Mahgoub Suliman; Ola Suliman; Ola Sharafeldin Mohamed Elhassan Hussein; Leena Yousif Omer Elbasheir; Abda Omer Osman Omer; Ola Nasir Mustafa Fadlalla; Roaa Ahmed Elobeid Dafaallah; Lena Husham Mohamed Ahmed (BMC Medical Education)
Abstract Background Neglected Tropical Diseases are a group of communicable diseases that are prevalent in tropical areas with poverty, and poor water sanitation and hygiene. Sudan is a low-income country with poor water sanitation hygiene services and medical facilities. The knowledge, attitude, and practice of medical students will influence their performance as future doctors to combat the neglected tropical diseases. Methodology we conducted a cross-sectional study among medical students in Khartoum State, Sudan. A multistage sampling technique was used and a total of 8 medical schools were selected as clusters. Based on the academic years, the study population was divided into proportionate strata. We collected the data through an online self-administered questionnaire with 2 sections. We calculated frequencies, percentages, and associations using Kruskal Wallis H, and linear regression analysis. Results A total of 407 participants from seven medical schools took part in the study. Approximately 34.2% of the participants did not know that neglected tropical diseases (NTDs) are classified as communicable diseases. In addition, 53.8% were unaware that ending NTDs is part of the 2030 Sustainable Development Agenda. Nearly 29.5% reported that they had never heard about NTDs in the context of Sudan. Furthermore, 48.4% of the respondents disagreed with the statement that Sudan has strong national policies to combat NTDs. On a more optimistic note, 80.6% agreed that medical students can contribute to ending NTDs. However, only 24.3% reported substantial participation in community awareness activities. Notably, 58.5% identified a lack of knowledge as the most significant barrier to engaging in NTD advocacy efforts. Conclusion Medical students play a crucial role in ending the neglected tropical diseases, not only as future doctors but as youth who have the energy to volunteer in advocacy activities. Addressing the lack of knowledge and practices among medical students through updating the curriculum and medical education strategies is crucial. Keywords: , , , , education